Gender Scripts and Children’s Performances that Reverberate in the Context of Early Childhood Education - de Moraes, Jéssica Tairâne; Felipe, Jade (Revista Brasileira de Estudos da Presença, 2024)
Based on Gender Studies and the Sociology of Childhood, this article seeks to understand and analyze the strategies that children establish to deal with the gender scripts addressed to them in everyday Early Childhood Education. The results of the analysis show that they seek more plural ways of living their experiences as girls and boys, even though they are educated based on binary concepts that try to impose a repeated control of children’s bodies. The research, of ethnographic inspiration, was developed based on participant observation with four-year-old children, in a public early childhood education school, in the Metropolitan Area of Porto Alegre/RS/Brazil.